Mothering & psychoanalysis : clinical, sociological and feminist perspectives - Bueskens, Petra, 1972- (Demeter Press, 2014)
""The collection of 23 essays provides an exciting snapshot of contemporary theorising on the maternal within psychoanalytic and social theory. The introduction serves as an excellent overview of this interdisciplinary field and its importance both to motherhood studies and broader feminist thinking. This book is a triumph!""--Assistant Professor Julie Kelso, Department of Philosophy and Literature, Bond University